2019
DOI: 10.1002/mar.21192
|View full text |Cite
|
Sign up to set email alerts
|

Okay, Google!: An empirical study on voice assistants on consumer engagement and loyalty

Abstract: E‐commerce shopping has gradually become a norm in consumers’ choice of shopping channel and part of this shopping process is aided by advance technologies including voice assistants (VA). There is a variety of artificial intelligence that is being developed in the market currently, and one of which has gradually gained its presence or information acquisition is the VA. In this paper, we propose a model that investigates the technology acceptance model constructs (perceived ease of use and perceived usefulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
179
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(231 citation statements)
references
References 69 publications
(93 reference statements)
6
179
0
2
Order By: Relevance
“…Several previous studies have also reported that perceived severity (e.g. failure of a service or risks from the performance of a product) increases the risk perception and has a detrimental effect on metrics such as customer loyalty [2] and trust [7,8]. Since the service provided by the VA devices is deeply integrated with newer technologies like IoT and cloud-computing, which does an invisible back-end processing of the collected data, hence in most cases the users are not aware of the potential and the prevalent risks (e.g.…”
Section: Major Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have also reported that perceived severity (e.g. failure of a service or risks from the performance of a product) increases the risk perception and has a detrimental effect on metrics such as customer loyalty [2] and trust [7,8]. Since the service provided by the VA devices is deeply integrated with newer technologies like IoT and cloud-computing, which does an invisible back-end processing of the collected data, hence in most cases the users are not aware of the potential and the prevalent risks (e.g.…”
Section: Major Findingsmentioning
confidence: 99%
“…Alexa from Amazon, Siri from Apple, Cortana from Microsoft, Google Assistant from Google, and Bixby from Samsung are some of the most popular commercially available VA's as of 2019. These voice-activated devices that are often tightly coupled with an Internet of Things (IoT) ecosystem in general are an asset, as they provide the users a more convenient and delightful way of doing certain things [2]. Due to their various advantages there is an increasing desire among the end users to adopt VA in their daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…SM is a way to generate companies and brands engagement in several actors and stakeholders, such as customers, suppliers and employees (Hollebeek et al, 2018). Customer engagement is a concept in evolution (Hollebeek, 2011) about how an actor can be profoundly interested and bounded in a company, in terms of trust, loyalty, commitment and confidence (Moriuchi, 2019), which include the B2B (Silva, Bradley, & Sousa, 2012;Diba, Vella, & Abratt, 2019) and the B2C contexts (Kesgin & Murthy, 2019). Online engagement can include how someone sees, follows and resends content on SM for his/her audience, helping a company to earn media, instead of buying it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, there is no agreement on adopting an enactive view of cognition to examine how voice assistant as a [semi] autonomous agent can enact consumers' cognition (e.g., Kyselo, 2018; Metta et al, 2010 ). Previous literature has scrutinized the embedded and embodied view of cognition to address how voice assistants influence consumers' decision-making ( Davenport et al, 2020 ; Pagani et al, 2019 ; Strayer et al, 2017 ; Moriuchi, 2019 ). Yet, it is still unclear how the auditory sense of voice assistants influences their auditory embodiment and consumers' responses ( Deng et al, 2019a , Deng et al, 2019b ; Schuetzler et al, 2018 ; Kramer et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research studies have shown that embedding communication ability ( Guzman, 2019 )—such as perceived ease of use and usefulness ( Moriuchi, 2019 )—through interactions with voice assistants enhances consumer trust ( Kim et al, 2018 ) and social image ( McLean and Osei-Frimpong, 2019 ) by engaging consumers to ( Pagani et al, 2019 ; Kachouie et al, 2014 ). Embedding emotion in voice (Schuller, 2018) further enhances social desirability ( Schuetzler et al, 2018 ) and consumers' believability ( Demeur et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%